Comparative analysis of whole plant, flower and root extracts of Chamomilla recutita L. and characteristic pure compounds reveals differential anti-inflammatory effects on human T cells - Lairikyengbam, Divya; Wetterauer, Bernhard; Schmiech, Michael; Jahraus, Beate; Kirchgessner, Henning; Wetterauer, Pille; Berschneider, Karina; Beier, Verena; Niesler, Beate; Balta, Emre; Samstag, Yvonne (Frontiers in Immunology, 2024)
Introduction: Chronic inflammation is a hallmark of chronic wounds and inflammatory skin diseases. Due to a hyperactive and prolonged inflammation triggered by proinflammatory immune cells, transitioning to the repair and healing phase is halted.T cells may exacerbate the proinflammatory milieu by secreting proinflammatory cytokines. Chamomilla recutita L. (chamomile) has been suggested for use in several inflammatory diseases, implying a capability to modulate T cells. Here, we have characterized and compared the effects of differently prepared chamomile extracts and characteristic pure compounds on the T cell redox milieu as well as on the migration, activation, proliferation, and cytokine production of primary human T cells.Methods: Phytochemical analysis of the extracts was carried out by LC-MS/MS. Primary human T cells from peripheral blood (PBTs) were pretreated with aqueous or hydroethanolic chamomile extracts or pure compounds. Subsequently, the effects on intracellular ROS levels, SDF-1a induced T cell migration, T cell activation, proliferation, and cytokine production after TCR/CD3 and CD28 costimulation were determined. Gene expression profiling was performed using nCounter analysis, followed by ingenuity pathway analysis, and validation at protein levels.The tested chamomile extracts and pure compounds differentially affected intracellular ROS levels, migration, and activation of T cells. Three out of five differently prepared extracts and two out of three pure compounds diminished T cell proliferation.In line with these findings, LC-MS/MS analysis revealed high heterogeneity of phytochemicals among the different extracts. nCounter based gene expression profiling identified several genes related to T cell functions associated with activation and differentiation to be downregulated. Most prominently, apigenin significantly reduced granzyme B induction and cytotoxic T cell activity.Our results demonstrate an anti-inflammatory effect of chamomilederived products on primary human T cells. These findings provide molecular explanations for the observed anti-inflammatory action of chamomile and imply a broader use of chamomile extracts in T cell driven chronic inflammatory diseases such as chronic wounds and inflammatory skin diseases. Importantly, the mode of extract preparation needs to be considered as the resulting different phytochemicals can result in differential effects on T cells.